Study on galling behaviour of HiPIMS deposited Mo/DLC multilayer coatings at ambient and elevated temperature - Kashyap A.; Harsha A.P.; Kondaiah P.; Barshilia H.C. (My University, 2025)
Galling has been a severe concern in oil – gas, automotive, and nuclear sectors. SS 304 steel is used in these industries despite its low galling resistance because it possesses good corrosion resistance properties. The threads of bolt, nut or a tapped hole and fasteners made of SS 304 experience severe damage due to galling or cold working. Therefore, the galling characteristics of the coated SS 304 samples were studied against the uncoated counterpart. A multilayer coating of molybdenum (Mo) and diamond like carbon (DLC) was deposited through dual sputtering using a high power impulse magnetron sputtering (HiPIMS) power source for graphite target and pulsed DC power source for Mo target. The Mo/DLC multilayer coating was optimized for antiwear and low friction properties. The evaluation of friction properties was done through a nanotribometer. The galling samples of SS 304 steel were prepared following the ASTM G196 standard, and the optimized coating was deposited on the galling samples. The adhesion strength of the coating was analyzed with the help of a nanoscratch tester. The galling behavior of coated and uncoated samples was investigated at room temperature (RT) and 300 °C. Galling damage was quantified by calculating the galling area on the galled sample. Image processing and computer vision tools were used to calculate the galled area. The tribopair having coated (Mo/DLC multilayer coating on SS 304) and the uncoated sample (SS 304) showed lower galled area than the tribopair containing both uncoated samples in every test conditions. At RT the coated sample failed at 15 MPa, whereas the uncoated samples failed at 5 MPa. Similar type of results were obtained when the samples were tested at 300 °C. The characterization of the coating and the mechanism of galling were studied in detail with the help of Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), nanoindentation, stereo-zoom optical microscopy, and scanning electron microscopy (SEM). © 2022 Elsevier B.V.